Protected Light-Trapping Silicon by a Simple Structuring Process for Sunlight-Assisted Water Splitting - Santinacci, Lionel; Diouf, Maimouna W.; Barr, Maissa K. S.; Fabre, Bruno; Joanny, Loic; Gouttefangeas, Francis; Loget, Gabriel (ACS Applied Materials and Interfaces, 2016)
Macroporous layers are grown onto n-type silicon by successive photoelectrochemical etching in HF-containing solution and chemical etching in KOH. This specific latter treatment gives highly antireflective properties of the Si surface. The duration of the chemical etching is optimized to render the surface as absorbent as possible, and the morphology of the as-grown layer is characterized by scanning electron microscopy. Further functionalization of such structured Si surface is carried out by atomic layer deposition of a thin conformal and homogeneous TiO2 layer that is crystallized by an annealing at 450 °C. This process allows using such surfaces as photoanodes for water oxidation. The 40 nm thick TiO2 film acts indeed as an efficient protective layer against the photocorrosion of the porous Si in KOH, enhances its wettability, and improves the light absorption of the photoelectrode. The macroporous dual-absorber TiO2/Si has a beneficial effect on water oxidation in 1 M KOH and leads to a considerable negative shift of the onset potential of ∼400 mV as well as a 50% increase in photocurrent at 1 V vs SCE.
Created from Fastlane, Scopus look-up
Keywords: atomic layer deposition; black silicon; electrochemical etching; nanostructuration; photoanode; photoelectrochemical cells; water splitting